2016
DOI: 10.1123/ijspp.2015-0444
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Reliability of a Specific Test of Stroke Performance in Table Tennis

Abstract: Results suggest that the specific test appears to be a simple and sensitive procedure to assess stroke performance in table tennis and that this test could be a relevant tool for coaches in table tennis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
1
24
0
5
Order By: Relevance
“…Indeed, the speed-accuracy trade-off hypothesis states that movements become less accurate the faster we performed them (Fitts, 1954). In accordance with this, a recent investigation calculated the ball speed–ball placement index and demonstrated that this index is relevant to discriminate the players with different levels of performance (Le Mansec et al, 2016).…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Indeed, the speed-accuracy trade-off hypothesis states that movements become less accurate the faster we performed them (Fitts, 1954). In accordance with this, a recent investigation calculated the ball speed–ball placement index and demonstrated that this index is relevant to discriminate the players with different levels of performance (Le Mansec et al, 2016).…”
Section: Introductionmentioning
confidence: 83%
“…Previous investigations have proposed several tests to evaluate the perceptual-motor skills (Faber et al, 2014a,b, 2015), aerobic and anaerobic parameters (Morel and Zagatto, 2008; Zagatto et al, 2008, 2011; Zagatto and Gobatto, 2012), and technical skills (Le Mansec et al, 2016) in table tennis players. Almost most of the tests for measuring physiological and technical skills were applied in a specific table tennis exercise (i.e., in an ecological task), their protocols were characterized by a continuous profile, with use of only forehand (FH) offensive strokes at balls sent by a robot at fixed areas of ball contact with the table.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations